2014
DOI: 10.1177/1538192714532814
|View full text |Cite
|
Sign up to set email alerts
|

Mentoring Experiences and Latina/o University Student Persistence

Abstract: This study examined the experiences of 17 Latina/o students who participated in a university mentoring program that included academic and cultural resources, involvement, and leadership opportunities. The goal was to understand their lived experiences and their own perceptions of their academic success and persistence. An interpretive phenomenological analysis was used with one-on-one interviews, revealing the following emergent themes: (a) common experiences providing benefits of mentoring, (b) common challen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 13 publications
2
28
0
Order By: Relevance
“…The basis of persistence is the power of will. Some research results reinforce the theory, namely factors that influence student persistence including social support (parents, peers), stress, socio-cultural integration, no time management, and no clear goals (Guan, et al, 2006;Lavigne, Vallerand, & Miquelon, 2007;Madhlangobe, et al, 2014, Salas, et al, 2014. In addition, the factors that influence students' persistence are the existence of economic factors, where male-type students withdraw or non-persist from women for fear of worrying about accumulating debt, so they choose to work and focus on his family (Cofer & Somers;Markle, 2015).…”
Section: Introductionmentioning
confidence: 74%
“…The basis of persistence is the power of will. Some research results reinforce the theory, namely factors that influence student persistence including social support (parents, peers), stress, socio-cultural integration, no time management, and no clear goals (Guan, et al, 2006;Lavigne, Vallerand, & Miquelon, 2007;Madhlangobe, et al, 2014, Salas, et al, 2014. In addition, the factors that influence students' persistence are the existence of economic factors, where male-type students withdraw or non-persist from women for fear of worrying about accumulating debt, so they choose to work and focus on his family (Cofer & Somers;Markle, 2015).…”
Section: Introductionmentioning
confidence: 74%
“…Models of retention in higher education also suggest that the sense of belonging and social integration that mentoring enhances are integral factors for academic persistence among Hispanic scientists (Chan, Yeh, & Krumboltz, 2015; Tinto, 1975, 2000). Unfortunately, many minority graduate students and junior faculty members report difficulty locating and accessing mentoring, networking, and other professional development opportunities within their home institutions (Bordes & Arredondo, 2005; Carozza, 2002; Salas, Aragon, Alandejani, & Timpson, 2014; Zalaquett & Lopez, 2006). …”
Section: Introductionmentioning
confidence: 99%
“…Research has found these types of programs improve student retention and graduation rates (Barefoot, 2005;Cambridge-Williams, Winsler, Kitsantas, & Bernard, 2013). Likewise, Latina/o students' persistence and degree attainment increase when they participate in these types of institutional programs (Berrios-Allison, 2011;Gonzales, Brammer, & Sawilowsky, 2015;Hurtado & Carter, 1997;Hurtado & Ponjuan, 2005;Salas, Aragon, Alandejani, & Timpson, 2014;Santos & Reigadas, 2002;Torres & Hernandez, 2010).…”
Section: List Of Figuresmentioning
confidence: 99%
“…Considering that, HSIs enroll a great proportion of first-generation and less academically prepared students (de los Santos & Cuamea, 2010) academic support and student services may play key roles in their educational attainment in the long-term. For example, advising, counseling, and mentoring programs offered by these units have been associated with Latinas/os' retention and graduation rates (Berrios-Allison, 2011;Salas et al, 2014;Torres & Hernandez, 2010). Also, some HSIs include students' family members to orientation and other activities "so they can understand what is required for getting a university education" (HSI president interview, in Santiago, 2004, p. 3) Furthermore, HSIs with long tradition of enrolling Latina/o students may have institutionalized programs to address the educational needs of Latinas/os.…”
Section: Expenditures and Educational Outcomes Of Latinas/osmentioning
confidence: 99%
See 1 more Smart Citation